(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the socio-philosophical aspects of the interaction between traditional and modern values in the context of globalization. While traditional values are largely derived from historical heritage, national culture, religious beliefs, and long-standing social norms of society, modern values are influenced by factors of technological progress, secularism, individualism, liberal democracy, and globalization. The process of interaction and integration between these two value systems is sometimes manifested in the form of harmonization, and sometimes in the form of opposition. The article analyzes from a philosophical point of view the influence of traditional and modern values on social life, their changing role in society and their inextricable connection with global trends. In particular, issues such as the problem of the preservation of national identity and cultural identity, the exchange of Western and Oriental values, the formation of new global humanistic principles and their impact on social consciousness are comprehensively covered.